A preliminary investigation: feasibility of an interactive multimedia application in increasing knowledge and awareness of cyber bullying among adolescents / Nadia Abdul Wahab and Wan Ahmad Jaafar Wan Yahaya - Abdul Wahab, Nadia; Wan Yahaya, Wan Ahmad Jaafar (UiTM Cawangan Perlis, 2016)
This paper describes a preliminary investigation of how the capabilities of an interactive multimedia application may be used to raise understanding and awareness towards cyber bullying among adolescents. Nine respondents were selected to participate in the interview ranging from three parents, three primary school students and three Secondary school students from Kedah and Perlis state of Malaysia. The findings of the interviews and literature reviews confirm that there is a lack of knowledge and awareness that needs to be addressed among adolescents especially in Malaysia. The paper also concludes that an interactive multimedia application needs to be designed and developed to increase knowledge and awareness on cyber-bullying among adolescents.